Decoding the research landscape of drug resistance and therapeutic approaches in head and neck cancer: a bibliometric analysis from 2000 to 2023 - Han, Qi; Shi, Junqi; Liu, Jiaojiao; Fu, Yang; Li, Zhongxun; Guo, Huina; Guan, Xiaoya; Xue, Xuting; Liu, Hongliang; Zhao, Liting; Zhang, Chunming (Frontiers in Pharmacology, 2024)
Introduction: Head and neck cancer is one of the most common tumors worldwide. However, drug resistance in its treatment has become a major factor limiting the efficacy. This study aims to comprehensively understand the current status of research in this field. Methods: The study analyzes papers related to therapeutic resistance in head and neck cancer published between 2000 and 2023 in the Web of Science Core Collection To achieve the research objectives, we searched the WoSCC for research and review papers on therapeutic resistance in head and neck cancer from 2000 to 2023, screened the English literature, and analyzed the research hotspots, academic collaborations, and trends in detail using tools such as Citespace, SCImago Graphica, and VOS viewer. Results: This study summarizes 787 head and neck cancer treatment resistance publications from WoSCC. The analysis showed that China and the United States are the major contributors in this field, and Grandis Jennifer R and Yang Jai-Sing are the key scholars. Keyword analysis showed that “cisplatin resistance” is a continuing focus of attention, while “Metastasis” and “Ferroptosis” may be emerging research hotspots. Literature clustering analysis pointed out that “Ferroptosis”, “Immunotherapy” and “ERK signaling” were the recent hotspots that received extensive attention and citations. Finally, we discuss the current status and challenges in drug-resistant therapies for head and neck cancer. Conclusion: This study is the first comprehensive bibliometric analysis of drug resistance in head and neck cancer. Reveals current trends and helps researchers grasp cutting-edge hotspots in the field.